A comparative analysis of clinicopathological factors and survival between esophageal basaloid squamous cell carcinoma and conventional esophageal squamous cell carcinoma. Issue 5 (May 2023) - Jiang, Dongxian; Wang, Haixing; Deng, Minying; Song, Qi; Liu, Yufeng; Peng, Rui; Xu, Lei; Su, Jieakesu; Xu, Chen; Hou, Yingyong
Abstract: Introduction: Recently, the number of diagnosed esophageal basaloid squamous cell carcinoma (EBSCC) has gradually increased. However, available data on EBSCC are limited to date. Methods: A total of 165 EBSCC (Cohort 1) and 515 conventional esophageal squamous cell carcinoma (ESCC) (Cohort 2) were retrospectively analyzed. Results: In Cohort 1, 70 cases only had invasive EBSCC component (42.4%, defined as Group 1), 73 cases had concomitant invasive ESCC component (44.2%, Group 2), and 22 had concomitant invasive poor-differentiated component (13.3%, Group 3). Lymph node metastasis rates of Group 3, Group 2 and Group 1 were ranked from high to low ( P  = 0.044). There were higher patient age ( P  = 0.047), smaller tumor size ( P  = 0.009), more nerve invasion ( P  < 0.001), and lower pTNM stage ( P  < 0.001) in EBSCC (Cohort 1), compared with ESCC (Cohort 2). In Cohort 1 and Cohort 2, pTNM stage was an independent prognostic factor for both DFS and OS. No significant survival difference was found between EBSCC (Cohort 1) and ESCC (Cohort 2) in pIA-B stage, pIIA-B stage, pIIIA-B stage and pIVA-B stage ( P  > 0.05). Conclusion: Our analysis of the largest EBSCC series from a single institution to date with conventional ESCC demonstrated that EBSCC carried a similar prognosis with ESCC in pIA-B stage, pIIA-B stage, pIIIA-B stage and pIVA-B stage. And pure EBSCC, didn't have poorer survival than mixed EBSCC with concomitant ESCC or other components. Our findings may be valuable in the better understanding of EBSCC's biological behaviors, and the related molecular mechanism is needed to be explored in the future.